Beginning iPhone 3 Development - Mark, Dave (Apress, 2012)
What an amazing journey! When we set out to write a book on iPhone development, it was purely a labor of love. We never dreamed our book would end up in so many people’s hands. Just imagine, our little book, available around the world. Who’d of thunk it? This wave of interest took us completely by surprise. And, of course, we are delighted by every bit of it. So, what’s new with this edition? Lots! For starters, we’ve gone through every single line of code and made whatever changes were necessary to bring each project into line with SDK 3. As you’d expect, we’ve gone through the text, too, so the explanations are all up-to-date. We’ve also gone through the errata from our Apress web page and the errors reported on our own web site, http://iphonedevbook.com, and we’ve done our best to scrub each and every error from the book. Of course, nothing is perfect, so please do report any errors you do find so we can continue to update the book through each new printing.